CRYSTALS enhancements: asymmetric restraints - Cooper, R; Thorn, A; Watkin, D (2012)
The traditional Waser distance restraint, the rigid-bond restraint and atomic displacement parameter (ADP) similarity restraints have an equal influence on both atoms involved in the restraint. This may be inappropriate in cases where it can reasonably be expected that the precision of the determination of the positional parameters and ADPs is not equal, e.g. towards the extremities of a librating structure or where one atom is a significantly stronger scatterer than the other. In these cases, the traditional restraint feeds information from the poorly defined atom to the better defined atom, with the possibility that its characteristics become degraded. The modified restraint described here feeds information from the better defined atom to the more poorly defined atom with minimal feedback.